Factors influencing the potency of marbofloxacin for pig pneumonia pathogens Actinobacillus pleuropneumoniae and Pasteurella multocida. (April 2017) - Dorey, L.; Hobson, S.; Lees, P.
Abstract: For the pig respiratory tract pathogens, Actinobacillus pleuropneumoniae and Pasteurella multocida, Minimum Inhibitory Concentration (MIC) of marbofloxacin was determined in recommended broths and pig serum at three inoculum strengths. MICs in both growth matrices increased progressively from low, through medium to high starting inoculum counts, 10 4, 10 6 and 10 8 CFU/mL, respectively. P. multocida MIC ratios for high:low inocula were 14:4:1 for broth and 28.2:1 for serum. Corresponding MIC ratios for A. pleuropneumoniae were lower, 4.1:1 (broth) and 9.2:1 (serum). MIC high:low ratios were therefore both growth matrix and bacterial species dependent. The effect of alterations to the chemical composition of broths and serum on MIC were also investigated. Neither adjusting broth or serum pH in six increments over the range 7.0 to 8.0 nor increasing calcium and magnesium concentrations of broth in seven incremental steps significantly affected MICs for either organism. In time-kill studies, the killing action of marbofloxacin had the characteristics of concentration dependency against both organisms in both growth matrices. It is concluded that MIC and time-kill data for marbofloxacin, generated in serum, might be preferable to broth data, for predicting dosages of marbofloxacin for clinical use. Highlights: MIC of marbofloxacin with both inoculum size and growth matrix dependent. Time-kill curves in broth and serum were concentration-dependent.